A visit to madinah: the prophet muhammad for little hearts - Khan, Saniyasnain (Goodword Press New Delhi, 2003)
"A Visit to Madinah: The Prophet Muhammad for Little Hearts" is a heartwarming and educational story that introduces young readers to the life and teachings of Prophet Muhammad (PBUH), fostering love, respect, and spiritual connection with the holy city of Madinah.